2003
DOI: 10.1002/em.10186
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic polymorphisms and the micronucleus frequency in buccal epithelium of adolescents living in an urban environment

Abstract: Micronuclei and other biomarkers were evaluated in oral cells from 11- to 16-year-old girls living in a foster home in the central area of México City. Variables analyzed for possible association with these biomarkers include smoking habits, body mass index, metabolic polymorphisms for NAT1 and GSTM1 and whether the cells were obtained from the cheek or pharynx. The results indicated that individuals having the NAT1*10 homozygous genotype showed a significant increase in chromatin buds and binucleated cells. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(9 citation statements)
references
References 22 publications
1
8
0
Order By: Relevance
“…These include scraping with a wood spatula (31,34,48,51,52,60,62,91,92), wood tongue depressor (12,32,43,45,56), cotton swab (42), short-bristle cytobrush (28,29,33,40,44,57,95,96), and toothbrush (95,96).…”
Section: Resultsmentioning
confidence: 99%
“…These include scraping with a wood spatula (31,34,48,51,52,60,62,91,92), wood tongue depressor (12,32,43,45,56), cotton swab (42), short-bristle cytobrush (28,29,33,40,44,57,95,96), and toothbrush (95,96).…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, the basal level of DNA damage in lymphocytes has been shown to be influenced by lifestyle conditions that can include diet, exercise, hormonal intake, smoking and drinking habits, indoor and outdoor pollution, occupational exposure, etc. [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, PBLs could also be used to assess the degree of DNA damage that is induced by abnormal (low or high) levels of some trace elements and metals, which has been linked in some studies with cancer development. In fact, over 90% of the biomonitoring studies have so far assayed human PBLs because they circulate in the body, and the cellular, nuclear, and metabolic state of the blood cells can reflect the overall extent of body exposure [18][19][20][21][22][23]. There is now strong evidence to indicate that a high level of DNA damage measured in lymphocytes reflects an elevated risk of cancer, although lymphocytes are not the cells that comprise solid tumors [18][19][20][21][22][23].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Few studies so far have investigated genetic damage in children exposed to air pollution [15][16][17][18][19]. In recent years, studies of MN frequency in the BM cells of children and young adults have shown cytogenetic damage in participants living in areas with high concentrations of particulate matter (PM) or oxidant pollutants [20][21][22][23][24][25]. Recently, Ceretti et al [25] found a higher frequency of MN in the exfoliated buccal cells (EBCs) of pre-school children living in a highly polluted town in the Po Valley in Italy than was observed in a pooled general population of the same age.…”
Section: Introductionmentioning
confidence: 99%